PENGARUH MOTIVASI, PENGAWASAN DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. SANDABI INDAH LESTARI (SIL) - Cindy Ayu Millania; Sri Ekowati (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
This study aims to determine the effect of supervisory motivation and compensation on work productivity of employees at PT. Sandabi Indah Lestari (SIL). This type of research is a quantitative descriptive research that is associative, the object of this research is all employees at PT. Sandabi Indah Lestari. The sampling method uses a non-probability technique, namely accidental sampling. The number of respondents in this study is 120 people. Methods of data collection using a questionnaire. The data analysis technique uses Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely t-test and f-test. The results of this study can be concluded that the motivation variable has a positive effect on employee work productivity, supervision has a positive effect on employee work productivity, compensation has a positive effect on employee work productivity and motivation, supervision and compensation together have a positive and significant effect on employee work productivity. Based on the results of this study, it shows that the development of supervisory motivation and compensation has a positive and significant effect on employee work productivity. Keywords:   Motivation of supervision and compensation on employee productivity.